Effect of dietary oregano oil on growth performance, disease resistance, intestinal morphology, immunity, and microbiota of hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) - Xin, Yu; Liu, Hao; Yan, Xiaobo; Huang, Weibin; Pan, Simiao; Zhou, Menglong; Lu, Baiquan; Tan, Beiping; Dong, Xiaohui; Yang, Yuanzhi (Frontiers in Marine Science, 2022)
The study aimed to investigate the effects of oregano oil (OO) supplement in the diet on the growth performance, disease resistance, immunity, and intestinal health of hybrid grouper. Six isonitrogenous and isolipidic diets were fed to the grouper with an initial weight of 19.10 ± 0.12 g for 8 weeks, of which the dietary OO levels were 0 (Control), 0.1 (OO-0.1), 0.3 (OO-0.3), 0.6 (OO-0.6), 0.9 (OO-0.9), or 1.2 (OO-1.2) g kg-1. The results showed that there were no significant differences in growth performance among the six groups, while the OO supplement could improve the disease resistance ability of grouper. Our findings have demonstrated that the OO supplement, especially 0.3 g kg-1, could improve the intestinal morphology via increasing the villus number and muscle thickness and elevate digestive enzyme activities such as those of amylase (AMS) and lipase. The 0.3-g kg-1 OO supplement also can activate the antioxidant defense system, reduce nuclear factor erythroid 2-related factor 2-like 2 (Nrf2)/Kelch-like-ECH-associated protein 1 (Keap1) expression, and then enhance the immune ability via acid phosphatase (ACP), lysozyme (LYS), complement C3 (C3), and tight junction-associated signaling pathways in hybrid grouper. Meanwhile, the relative abundance of Firmicutes and Bacteroidetes in the OO-0.3 group was significantly higher than that of Control group (P< 0.05), while the relative abundance of Proteobacteria showed a basically opposite trend (P< 0.05). These findings suggested that dietary OO supplementation could significantly improve intestinal health and induce the antioxidant defense system and immunity, which means that OO could be used as a functional feed additive to protect the intestine, and the appropriate addition level of OO should be 0.3 g kg-1.